Atmospheric iodine, selenium and caesium depositions in France : I. Spatial and seasonal variations - Roulier, Marine (2022)
The spatial distribution and seasonal variations of atmospheric iodine (I), selenium (Se) and caesium (Cs) depositions remain unclear and this precludes adequate inputs for biogeochemical models. We quantified total concentrations and fluxes of these elements in rainfalls from 27 monitoring sites in France with contrasted climatic conditions; monthly measurements were taken over one year (starting in 2016/09). Since speciation of I and Se can impact their behaviour in the environment, analysis of their inorganic compounds was also conducted. Our results showed that annual I concentrations in rainfall were much higher than those of Se and Cs (annual means = 1.56, 0.044 and 0.005 μg L-1, respectively). The annual iodine concentrations were highly positively correlated with those of marine elements (i.e. Na, Cl and Mg), involving higher I concentrations under oceanic climate than for transition, continental and mountainous ones. Furthermore, common patterns were found between Se concentrations and both marine and terrestrial components consistent with the various sources of Se in atmosphere. The association of Cs with two anthropogenic components (i.e. NH4+ and NO3-) used in agriculture supports the hypothesis of its terrestrial origin (i.e. from atmospheric dusts) in rainfall. We found higher rainfall concentrations of I during the warmest months for all climates. However, no specific seasonal trend occurred for Se and Cs. On annual average, rainfall contained mostly unidentified selenium compounds (inorganic Se proportions = 25-54%) and equal proportions of inorganic and unidentified I compounds. Concentrations of iodate were higher under oceanic climate consistent with an iodine marine-origin.